Immediate effects of ultrasound therapy on pain and plantar pressurein individuals with subacute ankle sprains: a randomized controlled trial - Suksri, Thongchai; Gaogasigam, Chitanongk; Boonyong, Sujitra (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. Despite the fact that ultrasound (US) therapy is not advised for acute ankle sprains, its therapeutic effects may bebeneficial for other stages of ankle sprains, such as a subacute ankle sprain. There is, however, a lack of evidence regarding theeffects of US on pain relief and functional improvement in subacute ankle sprains. Therefore, this study aimed to determine theimmediate effects of US on pain and plantar pressure in individuals with unilateral subacute ankle sprains.Methods. Fifty-four participants with unilateral subacute ankle sprains (aged 16–55 years) were recruited and randomly allocated into a treatment group (n = 27) and a control group (n = 27). The treatment and control groups received a single intervention session of US and an ineffectual US, respectively. Pain intensity during weight-bearing and static and dynamic plantarpressures were assessed before and after receiving the intervention.Results. In both groups, pain intensity was statistically reduced (p < 0.05) and clinically relevant. Although the maximum plantarpressure in the hindfoot during static conditions was statistically higher in the control group (p = 0.024), the values were stilllower than MDC95.Conclusions. A single treatment of US could clinically reduce pain, but it had no effect on altering plantar pressure in individualswith unilateral subacute ankle sprains.
Keywords: ankle; sprains; ultrasound; weight-bearing; pain